Penguatan Forum Anak Kabupaten Magelang Melalui Pelatihan Jurnalisme Seluler - Anisa Setya Arifina; Ascharisa Mettasatya Afrilia (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Mobile journalism skills are one of the important skills for the Magelang District Children's Forum (Fornagel) because of their active role as pioneers for fulfilling children's rights in the local area. In carrying out its role, Fornagel creates educational and informative messages that are distributed via Instagram and Youtube. These messages relate to the dangers of drugs, bullying, knowledge of pre-marital sexuality, and so on. This training aims to improve the ability of Fornagel management to use smartphones and social media to report social and cultural issues with journalistic principles. The method used to achieve this goal is the socialization and practice of mobile journalism which targets the ability to use communication technology in journalistic activities. The results of this community service activity show that there is an increase in knowledge and skills in using communication technology to carry out journalistic activities to support Fornagel's pioneering role.